Early, Subacute Coronary Stent Thrombosis: A Complication of COVID-19 Infection - Sadeq Tabatabai; Nooshin Bazargani; Kamaleldin Al-Tahmody; Jasem Mohammed Alhashmi (Dubai Medical Journal)
Soon after it was discovered in Wuhan, China, in December 2019, coronavirus disease 2019 (COVID-19) blow-out very fast and became a pandemic. The usual presentation is respiratory tract infection, but cardiovascular system involvement is sometimes fatal and also a serious personal and health care burden. We report a case of a 57-year-old man who was admitted with anterior wall acute myocardial infarction secondary to early coronary stent thrombosis and associated with COVID-19 infection. He was managed with primary coronary angioplasty and discharged home. Procoagulant and hypercoagulability status associated with severe acute respiratory syndrome coronavirus 2 infection is the most likely culprit. Choosing aggressive antithrombotic agents after coronary angioplasty to prevent stent thrombosis during the COVID-19 pandemic may be the answer but could be challenging.